The potential of soluble CD14 in discriminating nonalcoholic steatohepatitis from nonalcoholic fatty liver disease. Issue 6 (22nd February 2022) - Nakamura, Akihisa; Yamamoto, Koji; Takeda, Rei; Yamada, Ren; Kubo, Akinori; Morikawa, Kenichi; Ando, Sayaka; Shimazaki, Tomoe; Izumi, Takaaki; Umemura, Machiko; Kitagataya, Takashi; Shigesawa, Taku; et al.
Abstract: Background and Aims: Although various noninvasive markers and prediction formulas for nonalcoholic steatohepatitis (NASH) have been reported, they are of value only in the diagnosis of the advanced fibrosis stage of NASH. In this study, we evaluated soluble CD14 (sCD14) as a diagnostic marker for discriminating NASH from nonalcoholic fatty liver disease (NAFLD) using an animal model and clinical specimens. Methods: Serum sCD14 levels were measured in samples derived from mice with diet‐induced NASH and patients using an enzyme‐linked immunosorbent assay. Our cohort enrolled 126 patients with liver needle biopsy‐proven NAFLD. Results: The intestinal defense mechanism in NASH model mice was altered as a consequence of the unique gut environment. Elevated serum levels of sCD14 were observed in mice with diet‐induced NASH, and the condition of the liver was exacerbated as a result of exposure to gut‐derived endotoxin. We confirmed that the serum sCD14 levels in NAFL patients significantly differed from those in NASH patients. The area under the curve for distinguishing between NAFL and NASH was 0.891. Moreover, we found that serum sCD14 levels were weakly correlated with the inflammation grade based on the NAFLD activity score (NAS), the grade of fibrosis according to the Brunt fibrosis classification, and a positive correlation with the grade of ballooning based on NAS in patients with NAFLD. Conclusion: sCD14 could be a useful pathophysiological marker and diagnostic adjunct distinguishing NASH from NAFLD. The use of sCD14 may allow the screening and identification of high‐risk groups for NASH development and support early therapeutic interventions.